Can We Use Home Sleep Testing for the Evaluation of Sleep Apnea in Obese Pregnant Women?. (4th August 2019) - Facco, Francesca L.; Lopata, Victoria; Wolsk, Jennifer M.; Patel, Sanjay; Wisniewski, Stephen R.
Abstract : Objective . To evaluate the performance of a type III home sleep testing (HST) monitor including its autoscoring algorithm, in a population of obese pregnant women. Methods. This was an ancillary study of an ongoing prospective study of obese (BMI of ≥30) pregnant women. For the primary study, women undergo serial in-lab polysomnograms (PSG) during pregnancy. Sleep apnea was defined as an apnea hypopnea index (AHI) of ≥ 5 events/hour. A subgroup of women were asked to wear an ApneaLink HST device for 1 night, within 2 weeks of a late pregnancy PSG (≥ 28 weeks' gestation). The AHI obtained from PSG was compared to the AHI from the HST via autoscoring (HST-auto) as well as the AHI via technician scoring (HST-tech). We calculated Shrout Fleiss Fixed correlation coefficients (ICC) and looked at positive-positive and negative-negative agreement. Results. 43 women were recruited and we obtained 30 valid HST. The mean PSH AHI was 3.3 (±3.2, range 0.5-16.6). Six (20%) women had a positive PSG study. ICCs were 0.78 for HST-auto versus HST-tech, 0.76 for HST-auto versus PSG, and 0.70 for HST-tech versus PSG. Categorical agreement was also strong, with 24/30 (80.0%) for HST-auto versus HST-tech, 25/30 (83.3%) for HST-auto versus PSG, and 23/30 (76.7%) for HST-tech versus PSG. Conclusion. In obese women evaluated in late pregnancy, we found relatively high intraclass correlation and categorical agreement among HST-auto scores, HST-tech scores, and in-lab PSG results obtained within a two-week window. These results suggest that HST may be used to screen pregnant women for OSA.